ANALISIS KESALAHAN FONOLOGIS PADA PELAFALAN KONSONAN [l] : KAJIAN PSIKOLINGUISTIK - Nufaisa Nisrina; Amelia Firdaus; Sundawati Tisnasari (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study examines phonological symptoms related to mispronunciation of the consonant [l] in Indonesian using psycholinguistic studies. The main focus of this study is to analyze and understand the phonological characteristics of the letter [l], identify the causes of mispronunciation, and the impacts and strategies for improvement. The subject of the study was Dewi Wulandari who had difficulty pronouncing the consonant sound [l] correctly. The results of the study indicate that mispronunciation of the letter [l] can interfere with overall speaking and communication skills. The causes of this mispronunciation include physiological factors such as ankyloglossia (short tongue) and neurological factors such as brain nerve disorders. The habit of mispronunciation when starting to learn a language also contributes to this symptom. The impact of mispronunciation of the letter [l] includes unclear speech which hinders effective communication. To overcome this problem, special teaching techniques and strategies are needed to help speakers pronounce the correct sound. This study aims to improve the components of the language teaching and learning process through language error analysis, with the hope of improving effective and clear communication skills.